HLA-E/Mtb specific CD4+ and CD8+ T cells have a memory phenotype in individuals with TB infection - Voogd, Linda; Riou, Catherine; Scriba, Thomas J.; van Wolfswinkel, Marjolein; van Meijgaarden, Krista E.; Franken, Kees L. M. C.; Wilkinson, Robert J.; Ottenhoff, Tom H. M.; Joosten, Simone A. (Frontiers in Immunology, 2024)
IntroductionTuberculosis (TB) is the deadliest infectious disease worldwide and novel vaccines are urgently needed. HLA-E is a virtually monomorphic antigen presentation molecule and is not downregulated upon HIV co-infection. HLA-E restricted Mtb specific CD8+ T cells are present in the circulation of individuals with active TB (aTB) and Mtb infection (TBI) with or without HIV co-infection, making HLA-E restricted T cells interesting vaccination targets for TB.MethodsHere, we performed in-depth phenotyping of HLA-E/Mtb specific and total T cell populations in individuals with TBI and in individuals with aTB or TBI and HIV using HLA-E/Mtb tetramers.Results and DiscussionWe show that HIV co-infection is the main driver in changing the memory distribution of HLA-E/Mtb specific CD4+ and CD8+ T cell subsets. HLA-E/Mtb specific CD4+ and CD8+ T cells were found to circulate with comparable frequencies in all individuals and displayed expression of KLRG1, PD-1 and 2B4 similar to that of total T cells. The presence of HLA-E/Mtb specific T cells in individuals with aTB and TBI highlights the potential of HLA-E as a vaccine target for TB.